AUTHORITATIVE ECOLOGICAL CONVERGENCE BETWEEN HADITH AND PASANG RI KAJANG: WILĀYAT AL-AMR AS CONSTITUTIONAL LEGITIMACY FOR ENVIRONMENTAL GOVERNANCE - Ismail, Muhammad; Rusdi, M Ali; Amin, Muhammadiyah; Alwi, Zulfahmi; Usman Ali, Sitti Asiqah (Institut Agama Islam Negeri Bone, 2026)
This article examines the relationship between prophetic hadith and Pasang ri Kajang, the customary normative system of the Ammatoa Kajang community, through the framework of wilaayat al-amr in environmental governance. Situated at the intersection of hadith studies and Islamic constitutional thought, the study moves beyond textual interpretation to analyze how ecological hadiths function as sources of public authority in regulating collective environmental conduct. While previous scholarship has discussed Islamic environmental ethics and indigenous ecological traditions separately, their interaction as parallel normative authorities remains insufficiently explored. Using a qualitative normative-comparative method, this study analyzes selected ecological hadiths through dirāyah al-hadith, supported by maqashid al-shari‘ah and legal pluralism approaches. These findings are then compared with Pasang ri Kajang as a form of customary environmental law. The study finds that prophetic authority and Ammatoa customary leadership represent distinct yet functionally comparable forms of ecological governance. Prophetic authority operates universally, whereas Ammatoa authority functions locally as a socially autonomous institution that may also be recognized as a form of constitutional legitimacy within plural legal systems. This article argues that wilaayat al-amr should not be confined to formal state power alone, but may also include legitimate authority oriented toward public welfare (maslahah ‘ammah). By proposing the concept of authoritative ecological convergence, this study contributes to hadith studies, Islamic constitutional law, and environmental governance by offering a model through which religious norms and indigenous authority may coexist in promoting ecological sustainability. More broadly, the findings suggest that contemporary environmental policy should incorporate socially legitimate local authorities as strategic partners of the state in conservation governance. Such an approach may strengthen legal compliance, reduce jurisdictional conflict, and enhance the sustainability of environmental regulation.